Implementation of Class Management through Google Classroom during Online Learning in Elementary School - Priska Fadhila (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2021)
This study aims to determine the application of classroom management through Google Classroom during online learning at Muhammadiyah Kadisoka Elementary School. The research method used is a qualitative method with a descriptive approach. The data collection techniques used were interviews, observation, and documentation. Data analysis through several stages, namely the preliminary study stage, the data collection stage, the data reduction stage by looking for the equivalence of the obtained data, the data presentation stage, then closed with data verification. The validity of the data was obtained through a credibility test in the form of traingulation of data collection techniques and triangulation of data sources. The results showed that the implementation of class management through Google Classroom during online learning at Muhammadiyah Kadisoka Elementary School is a good way to manage classrooms using the features available in Google Classroom. The use of Google Classroom also allows teachers to carry out classroom management activities in order to create conducive, pleasant classroom conditions.